Pengaruh Model Pembelajaran Talking Stick Terhadap Hasil Belajar Ipa Di SMP Negeri 1 Hiliduho - Iman Kasih Lawolo; Agnes Renostini Harefa; Toroziduhu Waruwu; Hardikupatu Gulo (Departement of Mathematics Education, 2024)
Learning is an assistance provided by educators so that the process of acquiring knowledge and science, mastery of skills and habits, and the formation of attitudes and beliefs in students can occur. This study aims to determine whether or not there is an influence of the talking stick learning model on science learning outcomes at SMP Negeri 1 Hilihuho. This study is a quantitative study with a pre-experimental design. The population in the study were all students in grade VIII at SMP Negeri 1 Hilihuho totaling 62 people and the research sample was class VIII-B totaling 31 people selected using random sampling techniques. The instrument used in the study was in the form of a learning outcome test, where the test was divided into two types, namely a pre-test before giving treatment and a post-test after giving treatment in the form of implementing the talking stick learning model. Based on the results of data analysis using SPSS, it is known that the significance level value obtained is 0.00 or in other words that the significance level is <0.05. So specifically it can be concluded that there is an influence of the talking stick learning model on the learning outcomes of students at SMP Negeri 1 Hilihuho.